Technical Indicators to Evaluate the Degree of Large Clot Formation Inside the Membrane Fiber Bundle of an Oxygenator in an In Vitro Setup. Issue 2 (23rd October 2018) - Kaesler, Andreas; Hesselmann, Felix; Zander, Mark O.; Schlanstein, Peter C.; Wagner, Georg; Bruners, Philipp; Schmitz‐Rode, Thomas; Steinseifer, Ulrich; Arens, Jutta
Abstract: The most common technical complication during ECMO is clot formation. A large clot inside a membrane oxygenator reduces effective membrane surface area and therefore gas transfer capabilities, and restricts blood flow through the device, resulting in an increased membrane oxygenator pressure drop (dpMO). The reasons for thrombotic events are manifold and highly patient specific. Thrombus formation inside the oxygenator during ECMO is usually unpredictable and remains an unsolved problem. Clot sizes and positions are well documented in literature for the Maquet Quadrox‐i Adult oxygenator based on CT data extracted from devices after patient treatment. Based on this data, the present study was designed to investigate the effects of large clots on purely technical parameters, for example, dpMO and gas transfer. Therefore, medical grade silicone was injected into the fiber bundle of the devices to replicate large clot positions and sizes. A total of six devices were tested in vitro with silicone clot volumes of 0, 30, 40, 50, 65, and 85 mL in accordance with ISO 7199. Gas transfer was measured by sampling blood pre and post device, as well as by sampling the exhaust gas at the devices' outlet at blood flow rates of 0.5, 2.5, and 5.0 L/min. Pre and post device pressure was monitored to calculate the dpMO at the different blood flow rates. The dpMO was found to be a reliable parameter to indicate a large clot only in already advanced "clotting stages." The CO2 concentration in the exhaust gas, however, was found to be sensitive to even small clot sizes and at low blood flows. Exhaust gas CO2 concentration can be monitored continuously and without any risks for the patient during ECMO therapy to provide additional information on the endurance of the oxygenator. This may help detect a clot formation and growth inside a membrane oxygenator during ECMO even if the increase in dpMO remains moderate.